Des stratégies d’usage des technologies numériques au secours de pratiques communicationnelles frustrantes - Emilie Blanc (Communication, 2017)
The Toulouse Financial Centre (La Poste Group) has implemented a new communications plan aimed at the digital acculturation of mail clerks. The author conducted action research on preventing the psychosocial risks associated with this digital acculturation. She shows how this change did not represent a psychosocial risk factor thanks to the particularly innovative measures taken. However, participant observations show that although not an integral part of the initial project, the social workers assigned to help mail clerks embrace digital were themselves exposed to psychosocial risks in their professional practice.